PERANCANGAN TURBIN ANGIN SUMBU VERTIKAL SEBAGAI PEMBANGKIT LISTRIK (SKALA LABORATORIUM) - Meidian Pratama, Risco; arifin, Fatahul; Sundari, Ella; Okviyanto, Toni; Yahya, Yahya; Martomi, Eka Satria; Firdaus, Firdaus (MACHINERY Jurnal Teknologi Terapan, 2023)
Wind is one of the newest energy sources that is becoming increasingly popular nowadays. The use of wind energy can be converted into electrical energy for wind turbine cells. However, there are two types of wind turbines, namely horizontal and vertical. Holistic wind turbines are usually used in one direction while vertical wind turbines are used in all directions. The shape of the blades and the number of wind turbine blades greatly influence the power produced. So the research this time is to find out the influence of the blade shape that has been varied and the number of blades with wind speeds of 2.5 m/s, 3 m/s, 3.5 m/s and 4 m/s on the resulting generator power so that the efficiency results What has been obtained can be designed to design wind turbines with varied blade shapes. Testing was carried out in a laboratory designed independently with a wind source using a fan and Dimmelr air conditioner. The results of tests that have been carried out have the highest gelnelratolr power known at 4 blades with a wind speed of 4 m/s with a power value of 0.34 watts while the smallest gelnelratolr power is known at 2 blades with a wind speed of 2.5 m/s with rated power 0.04 Watt. So that the research results from all the tests, the highest efficiency value was obtained at 4 blades with a wind speed of 2.5 m/s with a value of 24.4% and the lowest efficiency value was obtained at 2 blades with a wind speed of 3 m/s 6, 4 %.